(untitled) (Książnica Śląska, 2025)
The main topic of the text are bibliographic works carried out by the Silesian Library and its predecessors (the Library of the Silesian Parliament and the Public Library of Silesia). The author traced the history of these activities from the pre-war years to the present day. She described the creation of Silesian retrospective and current bibliographies. In the article are presented the changes that occurred in collecting, selecting and recording bibliographic material. It is also discussed the current state of bibliographic work carried out within the Silesian Collections Department of the Silesian Library.